2017
DOI: 10.1590/0104-07072017005100015
|View full text |Cite
|
Sign up to set email alerts
|

Sexually Transmitted Diseases: Knowledge and Sexual Behavior of Adolescents

Abstract: Objective: to evaluate the sexual knowledge and behavior of adolescents about Sexually Transmitted Diseases.Method: a descriptive, observational and quantitative study with a convenience sample of 532 adolescents aged between 10 and 19 years old. An individual questionnaire on sexually transmitted diseases was applied. The STATA 11.1 program was used for data analysis.Results: 89.2% of the teenage girls and 90.3% of the teenage boys were able to properly define the concept of a STD. Condom use is the most effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
1
20

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 20 publications
3
20
1
20
Order By: Relevance
“…3 In addition, studies indicate that condoms are understood by the population as the most effective method to prevent STIs. 24 As a limitation of the study it is possible to highlight the centralization of the sample in a geographical location as well as the response bias for behavior-related issues and adoption of preventive measures.…”
Section: /12mentioning
confidence: 99%
“…3 In addition, studies indicate that condoms are understood by the population as the most effective method to prevent STIs. 24 As a limitation of the study it is possible to highlight the centralization of the sample in a geographical location as well as the response bias for behavior-related issues and adoption of preventive measures.…”
Section: /12mentioning
confidence: 99%
“…The health-seeking behavior of STIs may largely depend on knowledge about STIs [ 14 ]. Several studies have been conducted worldwide regarding knowledge about STIs and reported that 74.7% in India [ 15 ], 92.4% in Nigeria [ 16 ], 89.9% in Brazil [ 17 ], 98% in Tanzania [ 18 ], 88.5% in Jimma, Ethiopia [ 19 ], 79% in Dhaka, Bangladesh [ 20 ], 86.6% in Malaysia [ 21 ], 74% medical and 61.6% non-medical university students in Pakistan [ 22 ], 83.1% in Turkey [ 23 ], 68.3% in Klang Valley, Malaysia [ 24 ], 27% in Udupi Taluk, India [ 25 ], and 70.1% in northern Cape Province, South Africa [ 26 ] of the respondents had good knowledge of STIs. The factors that influence knowledge of STIs are diverse and include age, sex, residence, marital status, academic year, and acquiring information from friends/internet and mass media [ 5 , 18 , 27 - 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…No casamento, a relação de exclusividade e o pacto de fidelidade com as esposas determinam o uso do preservativo apenas em situações especiais. Em outras palavras, a camisinha constitui-se como um método provisório (14) .…”
Section: Resultsunclassified